Resveratrol Inhibits Periodontitis‐Related Bone Loss in Rats Subjected to Cigarette Smoke Inhalation. Issue 8 (1st August 2017) - Ribeiro, Fernanda V.; Pino, Danilo S.; Franck, Felipe C.; Benatti, Bruno B.; Tenenbaum, Howard; Davies, John E.; Pimentel, Suzana P.; Casarin, Renato C.; Cirano, Fabiano R.; Casati, Marcio Z.
Abstract : Background: Alternative therapeutic approaches have been explored to modulate host response to periodontal disease. Knowledge of new strategies to treat periodontitis is particularly relevant in patients presenting augmented risk to periodontitis, such as smokers. The aim of this study is to investigate the impact of resveratrol (RESV) on progression of experimental periodontitis (EP) in the presence of cigarette smoke inhalation (CSI). Methods: Rats were assigned to one of three groups: 1) CSI+RESV (n = 20); 2) CSI+placebo (n = 20); and 3) non‐CSI (n = 20). CSI was initiated 1 week prior to initiation of RESV or placebo administration (systemically for 30 days) and was continued until the end of the study. EP was induced around the first mandibular and second maxillary molars using ligatures. Specimens from the mandible were processed for morphometric and microcomputed tomography examination of bone volume/levels. Gingival tissues surrounding mandibular molars were collected for quantification of interleukin (IL)‐1β, IL‐4, IL‐6, IL‐17, and tumor necrosis factor‐α using an assay system. Additional analyses of immunoinflammatory mediator performance (T‐helper Type 17 [Th17]/Th2 and Th1/Th2 cell levels) were performed according to Th cell responses in gingival tissues. Gingival tissues of maxillary molars were subjected to real‐time polymerase chain reaction for assessment of osteoprotegrin, runt‐related transcription factor‐2, receptor activator of nuclear factor‐kappa B ligand (RANKL), sclerostin, and Dickkopf Wnt signaling pathway inhibitor 1 levels. Results: Higher linear alveolar bone loss (ABL) and lower interradicular bone density were detected in ligated molars in the CSI+placebo group ( P <0.05). IL‐4 level was the highest, and Th17/Th2 levels were the lowest in RESV‐treated rats compared with placebo rats ( P <0.05). RESV reduced expression of messenger RNA for RANKL in animals receiving CSI ( P <0.05). Conclusion: RESV inhibits EP and CSI‐induced supporting ABL and has a beneficial effect on osteo‐immunoinflammatory markers.